Dental Pulp Stem Cells on Implant Surface: An In Vitro Study. (24th March 2021) - Laino, Luigi; La Noce, Marcella; Fiorillo, Luca; Cervino, Gabriele; Nucci, Ludovica; Russo, Diana; Herford, Alan Scott; Crimi, Salvatore; Bianchi, Alberto; Biondi, Antonio; Laino, Gregorio; Germanà, Antonino; et al.
Abstract : In the field of biology and medicine, one hears often about stem cells and their potential. The dental implant new surfaces, subjected to specific treatments, perform better and allow for quicker healing times and better clinical performance. The purpose of this study is to evaluate from a biological point of view the interaction and cytotoxicity between stem cells derived from dental pulp (DPSCs) and titanium surfaces. Through the creation of complex cells/implant, this study is aimed at analyzing the cytotoxicity of dental implant surfaces (Myth (Maipek Manufacturer Industrial Care, Naples, Italy)) and the adhesion capacity of cells on them and at considering the essential factors for implant healing such as osteoinduction and vasculogenesis. These parameters are pointed out through histology (3D cell culture), immunofluorescence, proliferation assays, scanning electron microscopy, and PCR investigations. The results of the dental implant surface and its interaction with the DPSCs are encouraging, obtaining results increasing the mineralization of the tissues. The knowledge of this type of interaction, highlighting its chemical and biological features, is certainly also an excellent starting point for the development of even more performing surfaces for having better healing in the oral surgical procedures related to dental implant positioning.